ESTIMATION OF HETEROSIS IN DIFFERENT CROSSES OF BREAD WHEAT (TRITICUM AESTIVUM L.) - SINGH, MAMTA; DEVI, E. LAMALAKSHMI; AGLAWE, SUPRIYA; KOUSAR, NAGMA; BEHERA, CHANDANA (The Bioscan, 2013)
Here we report some of the heterotic wheat crosses produced by crossing fifteen parents in a line x tester mating scheme. Analysis of variance revealed significant differences at 1% level of significance among the genotypes. Manifestation of heterosis was done over mid parent, better parent and the two standard checks i.e. UP 2684 and PBW 343. The generated data registered JUPIBJY/URES X UP 2572 as the best heterotic hybrid for harvest index against the checks UP 2684 and PBW 343 with the values of 27.39% and 50.54% respectively. Likewise HP 1749 X UP 2572 showed maximum heterosis (18.66%) over the check PBW 343. The data provides information on heterotic advantage of important yield and associated components. The highest heterotic genotypes can be exploited in future breeding programs to attain self-sufficiency in food grains. However, comprehensive field evaluation over locations and years is advocated for the crosses having significant heterosis before their commercial exploitation.